TINGKAT PARTISIPASI MASYARAKAT TERHADAP PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR JALAN DESA PELUKAHAN KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Tri Musliyatun; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in the Pelukahan village Kuantan Hilir Seberang Kabupaten Kuantan Singingi. This study aims to determine how the public participation in the implementation of road infrastructure construction and to know what are the factors that influence public participation in the implementation of road infrastructure construction. This study, entitled "Public Participation Rate of Society for Implementation of Construction Road Infrastructure Pelukahan Village Kuantan Hilir Seberang Kabupaten Kuantan Singingi Riau Province". The main problem in this research is how the public participation in the implementation of road infrastructure construction and what are the factors that influence public participation in the implementation of road infrastructure construction. The samples in this research is using purposive sampling technique. Amount of total population in 2014, which amounted to 245 families (KK), samples taken were 30 families (KK) which has represented the population predetermined criteria. The method used is quantitative method with a descriptive approach. Instrument filtering data used are observation, documentation and interview. The results have generally been carried out by the researcher, the researcher can say that public participation in the implementation of road infrastructure construction Pelukahan Village are low by category never participate are contributing materials totaling 25 respondents (83%), because they assume that all material has been given by the government and the other reason is they are just hard to build his house let alone to donate materials to the road construction. Factors that affect the implementation of road infrastructure constructionis the education factor and the same amount of work that is 18 respondents (60%). Education and employment factors are very influential because they are educated will definitely get the job also high, therefore their participation due to lower prioritize their personal work.Keywords: Participation, Community, Construction